Photocatalytic CO2 Reduction Using Various Heteroleptic Diimine-Diphosphine Cu(I) Complexes as Photosensitizers - Yamazaki, Yasuomi; Onoda, Takayuki; Ishikawa, Jun; Furukawa, Shota; Tanaka, Chinatsu; Utsugi, Tomoya; Tsubomura, Taro (Frontiers in Chemistry, 2019)
The development of efficient redox-photosensitizers based on the earth-abundant metal ions as an alternative towards noble- and/or rare-metal based photosensitizers has been desired. In recent years, heteroleptic diimine-diphosphine Cu(I) complexes have been well investigated as one of the most remarkable candidates because of their great potentials as efficient photosensitizers. Here, we investigated the effects of the structure of the diphosphine ligands on the photosensitizing abilities using a series of Cu(I) complexes bearing 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (dmpp) and various diphosphine ligands in order to explore the suitable structure for the photosensitizing reactions. The number of methylene chains between the two phosphorous atoms in the diphosphine ligands was systematically changed from two to four, and the relationship between the length of the carbon chains and the photosensitizing abilities were investigated by conducting photocatalytic CO2 reduction with the Cu(I) complexes as photosensitizers. Turnover frequencies of the CO2 reduction drastically increased with increasing the length of the carbon chains. The systematic study herein reported suggests that the large P-Cu-P angles should be one of the most important factors for enhancing the photosensitizing abilities.